(untitled) (Herald of Journalism, 2018)
This article refers to the history of publishing, its stage of development and the impact of the Japanese publishing industry in the world literature today. Milestones in the history of publishing, which makes a great contribution to world literature today will focus on the Japanese publishing industry. Economic development, science and technology, culture, Japan has made great strides in terms of state formation with a very high level of education, thanks, including advances in publishing activities. We get information on how to develop industry-specific universal publishers.